Influence of antenatal smoking exposure on the newborn response to a hypoxic challenge. (24th May 2012) - Ali, K; Wolff, K; Bhat, R; Rafferty, G; Hannam, S; Greenough, A
Abstract : Aims: Infants of mothers who smoked during pregnancy have an increased risk of sudden infant death; a possible explanation is that such infants have neurodevelopmental abnormalities of ventilatory control. Our aim was to test the hypothesis that infants of mothers who had smoked antenatally compared to infants of non-smoking mothers would have a poorer ventilatory response to hypoxia. Methods: Infants were recruited before maternity unit discharge and assigned to one of two groups based on maternal smoking history. A pneumotachograph and face mask were placed over the infant's mouth and nose. During quiet sleep, the infants were switched from breathing room air to 15% oxygen (hypoxic challenge), which was maintained for five minutes unless the oxygen saturation level fell below 85%. Changes in oxygen saturation, heart rate, respiratory rate, tidal and minute volume and end tidal CO2 (ETCO2) were assessed. Results: Ten infants of smoking mothers (median gestational age of 39 (36-41) weeks) and 10 infants of non smoking mothers (39 (37-42) weeks) were studied. The median birth weight of the infants of the smoking mothers was lower than that of infants of the non-smoking mothers (2450 (1924-3790) grams versus 3299 (2560-4320) grams, p=0.04). The infants were studied at similar postnatal ages (median 30 (10-120) versus 32 (10-100) hours), p=0.7. The two groups had comparable baseline tidal breathing, oxygen saturation, heart rate and ETCO2 levels. In response to the hypoxic challenge, the two groups had similar falls in their oxygen saturation and increases in heart rate. There was a biphasic response in minute ventilation to the hypoxic challenge. There was no significant differences in the initial percentage increase in minute ventilation between the two groups (median 29% (range 17-40) versus 23% (2-35), p=0.23, but the subsequent percentage decrease in minute volume in the infants of the smoking mothers was greater than that of the infants of the non-smoking mothers (median 32 % (range 0-99) versus 0%(−20-32)), p=0.03. Conclusion: These results suggest intrauterine exposure to tobacco smoking may result in impairment of the infant peripheral chemoreceptor response.